THE EFFECT OF WORKPLACE SPIRITUALITY DIMENSIONS ON ORGANIZATIONAL COMMITMENT WITH PERCEIVED ORGANIZATIONAL SUPPORT AS MODERATING VARIABLE - Diaz Haryokusumo (Jurnal Dinamika Manajemen)
The aims of this study are to test the effect of workplace spirituality dimensions (inner life, meaningful work, and condition for community) on organizational commitment (affective, continuance, and normative) and also to test the moderating effect of perceived organizational support. 130 questionnaires were collected from six organizations in Yogyakarta.The result of this research shows the workplace spirituality dimensions have positive effect on affective commitment. Testing of moderation effect shows perceived organizational support does not moderate the positive effect of workplace spirituality dimensions on components of organizational commitment. Based on this research, condition for community has the biggest effect on affective commitment, while inner life has biggest effect on normative and continuance commitment. Implication for management theory and practice are discussed.